2014
DOI: 10.1530/endoabs.35.p696
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic steatohepatitis as a novel player in metabolic syndrome-induced erectile dysfunction: an experimental study in the rabbit

Abstract: a b s t r a c tA pathogenic link between erectile dysfunction (ED) and metabolic syndrome (MetS) is now well established. Nonalcoholic steatohepatitis (NASH), the hepatic hallmark of MetS, is regarded as an active player in the pathogenesis of MetS-associated cardiovascular disease (CVD). This study was aimed at evaluating the relationship between MetS-induced NASH and penile dysfunction. We used a non-genomic, high fat diet (HFD)-induced, rabbit model of MetS, and treated HFD rabbits with testosterone (T), wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…In a recent study on the nongenomic, high-fat dieteinduced model of MetS in rabbits (characterized by hyperglycemia, glucose intolerance, hypercholesterolemia, hypertriglyceridemia, hypertension, increased visceral fat mass, hypogonadotropic hypogonadism, and NASH) that closely resembles the human MetS phenotype, MetS-induced NASH was suggested to play an active role in the pathogenesis of ED, likely via TNFa. 19 Moreover, treatment of those rabbits with infliximab, a selective antiTNFa antibody and obeticholic acid, a farnesoid X receptor agonist resulted in amelioration of liver damage and improvement of penile responsiveness to acetylcholine. 19 The role of increased TNFa, a proinflammatory cytokine, in NAFLD has long been studied by many researchers including our group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study on the nongenomic, high-fat dieteinduced model of MetS in rabbits (characterized by hyperglycemia, glucose intolerance, hypercholesterolemia, hypertriglyceridemia, hypertension, increased visceral fat mass, hypogonadotropic hypogonadism, and NASH) that closely resembles the human MetS phenotype, MetS-induced NASH was suggested to play an active role in the pathogenesis of ED, likely via TNFa. 19 Moreover, treatment of those rabbits with infliximab, a selective antiTNFa antibody and obeticholic acid, a farnesoid X receptor agonist resulted in amelioration of liver damage and improvement of penile responsiveness to acetylcholine. 19 The role of increased TNFa, a proinflammatory cytokine, in NAFLD has long been studied by many researchers including our group.…”
Section: Discussionmentioning
confidence: 99%
“…19 Moreover, treatment of those rabbits with infliximab, a selective antiTNFa antibody and obeticholic acid, a farnesoid X receptor agonist resulted in amelioration of liver damage and improvement of penile responsiveness to acetylcholine. 19 The role of increased TNFa, a proinflammatory cytokine, in NAFLD has long been studied by many researchers including our group. 20 Hence, an ongoing hepatic inflammation, as reflected in our patients' liver biopsies may count for the triggering factor of the accompanying vascular disease in NAFLD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, hsCRP [38] and leukocyte count were measured. Liver enzymes were determined since the liver is the source of TNF-α [39].…”
Section: Methodsmentioning
confidence: 99%
“…Insulin resistance is the underlying mechanism of metabolic syndrome and is also the most prevalent risk factor for NAFLD, a condition strongly associated with hepatic and adipose tissue insulin resistance, as well as reduced wholebody insulin sensitivity Interestingly, MetS induced inflammation within the liver, also known as steato-hepatitis, has been very recently elucidated in an experimental study in the rabbit [14]. Surprisingly, a recent cross-sectional study showed a new link between the presence of BPH/LUTS, MetS and NAFLD, demonstrating a 2.0-fold risk of having moderate-severe LUTS in men with both manifestation (OR ¼ 2.10, p50.01) [15].…”
mentioning
confidence: 99%